2013
DOI: 10.4028/www.scientific.net/amr.633.224
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene Based Nanomaterials for Biomedical Applications: Engineering, Functionalization and Characterization

Abstract: Since their discovery in 1985, fullerenes have attracted considerable attention. Their unique carbon cage structure provides numerous opportunities for functionalization, giving this nanomaterial great potential for applications in the field of medicine. Analysis of the chemical, physical, and biological properties of fullerenes and their derivatives showed promising results. In this study, functionalized fullerene based nanomaterials were characterized using near infrared spectroscopy, and a novel method - Aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…In the medical field, aquaphotomics was proposed for in vivo therapy monitoring of topical cream effects [73,74], for monitoring of dialysis efficacy [67] and diagnosis of several diseases: cancer [67], diabetes and coronary heart disease [75]. These applications utilize the concept of a water spectral pattern as an integrative biomarker that offers significant advantage compared to traditional ways of therapy monitoring or diagnostic practices in medicine.…”
Section: Aquaphotomics—innovative Knowledge Leads To Innovative Apmentioning
confidence: 99%
See 1 more Smart Citation
“…In the medical field, aquaphotomics was proposed for in vivo therapy monitoring of topical cream effects [73,74], for monitoring of dialysis efficacy [67] and diagnosis of several diseases: cancer [67], diabetes and coronary heart disease [75]. These applications utilize the concept of a water spectral pattern as an integrative biomarker that offers significant advantage compared to traditional ways of therapy monitoring or diagnostic practices in medicine.…”
Section: Aquaphotomics—innovative Knowledge Leads To Innovative Apmentioning
confidence: 99%
“…More recent studies exploring the state of water in hydrogel materials of soft contact lenses [94,95,96] revealed that the water spectral pattern holds information even about the state of polymer network and protein deposits on the surfaces of worn contact lenses. Other aquaphotomics studies showed how nanomaterials shape the water matrix, as in the case of fullerene-based nanomaterials that act as water structuring elements when present in very low concentrations [73,74,97]. In nanotechnology and nanomedicine, aquaphotomics could lead to novel findings due to the fact that with decreasing size, the available active surface interacting with water playing a significant role increases.…”
Section: Aquaphotomics—innovative Knowledge Leads To Innovative Apmentioning
confidence: 99%
“…Fullerenes are extensively studied in a number of applications such as organic photovoltaics (Brabec et al, 2010 ; Kirner et al, 2014 ), gas storage (Gadd et al, 1999 ), and molecular sensing (Baena et al, 2002 ; Sherigara et al, 2003 ). In the last 30 years fullerenes, alongside CNTs, were considered among the cutting-edge nanomaterials for biomedical applications: they were proposed as oxidative damage protecting agents, photosensitizers for photodynamic therapy of cancer, antiretroviral agents and as drugs and gene delivery vectors (Bakry et al, 2007 ; Tykhomyrov et al, 2008 ; Partha and Conyers, 2009 ; Chen et al, 2012 ; Matija et al, 2013 ). Fullerenes also were the pioneering carbon nanomaterials investigated in vivo for their potential applications in the therapy of brain diseases.…”
Section: Fullerenesmentioning
confidence: 99%
“…In the last few years, however, the scientific community has been showing a growing interest in graphene and graphene oxide (Zhang Y. et al, 2012 ; Zhang H. et al, 2013 ; Yang et al, 2013a ), nanodiamonds (Mochalin et al, 2011 ; Perevedentseva et al, 2013 ) and carbon dots (Shen et al, 2012 ; Luo et al, 2013 ). On the opposite fullerenes, which attracted a lot of attention in the past, are now experiencing a gradual loss of interest due to concerns regarding toxicity (Zhu et al, 2006 ; Kolosnjaj et al, 2007 ; Partha and Conyers, 2009 ; Matija et al, 2013 ). Carbon nano-onions also are attracting attention for their possible biomedical application (Ghosh et al, 2011 ; Sonkar et al, 2012 ; Yang M. et al, 2013 ; Bartelmess et al, 2014 , 2015b , c ; Giordani et al, 2014 ; Frasconi et al, 2015a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the number of fullerene‐based amphiphiles for diagnostics and biomedical applications has increased remarkably . For instance, modified fullerenes have been implemented for biomedical imaging, drug and gene delivery systems, which are potentially applicable to combat various diseases, and, as producers of reactive oxygen species, intended for usage as agents in photodynamic therapies . Furthermore, amphiphilic fullerene derivatives show a high activity against pathogens .…”
Section: Schematic Representation Of Fpsmentioning
confidence: 99%